Wishful thinking: processes of meaning in the discourse of the learning crisis of multilateral organizations (Práxis Educativa, 2022)
In this paper, it is analyzed the discourse of the learning crisis in the documents published by multilateral bodies: World Bank, UN, UNESCO and UNICEF, between 2013 and 2021. Based on Stephen Ball’s Theory of Political Networks and Norman Fairclough’s Critical Discourse Analysis, it was identified that the announced crisis moves in an interstate perspective, from the idea of a global phenomenon, justified by local problems, centered on the teacher’s agency and the student. It is a rhetorical discourse, impregnated with wishful thinking (fallacies of hope), highlighting: the school and the teachers are blamed for the crisis; organizations have solutions to reduce it; the confrontation requires partnerships involving governments, school community, third sector and private sector, under the leadership of organizations. The discourses are structured in a Persuasive Strategic Cycle – commotion, seduction, promise and sale – to convince readers and organize the actors of education policy around the network governance.Keywords: Education Policy. Learning crisis. Critical Discourse Analysis.